Comparison of optic disc measurements by Heidelberg Retina Tomograph and manual planimetric techniques - Vihanninjoki, Kyösti; Tuulonen, Anja; Burk, Reinhard; Airaksinen, P. Juhani (Acta ophthalmologica Scandinavica, 1997)
ABSTRACT. The inner edge of the scleral ring is used as a reference plane for manual, computer assisted optic disc measurements. As it is possible to identify this level with the Heidelberg Retina Tomograph, our aim was to compare manual measurements to those taken with the Heidelberg Retina Tomograph. The material of this pilot study consisted of 12 eyes of 12 patients with early glaucomatous optic disc, retinal nerve fiber layer and/or visual field abnormalities. Measurements of the optic disc and neuroretinal rim area were obtained using our manual planimetric techniques, and the Heidelberg Retina Tomograph. The mean optic disc areas measured smaller with the Heidelberg Retina Tomograph than with the manual techniques (average difference 0.13 mm2; p<0.05). The neuroretinal rim area measurements and cup-to-disc area ratio using manual and Heidelberg Retina Tomograph techniques did not differ statistically significantly from each other. With the scleral ring as a reference plane, comparable optic disc measurements can be obtained with manual and laser techniques.